The Community Service on Antibiotics Use at Banjar Pinda Gianyar - Manik Partha Sutema Ida Ayu; Ni Putu Aryati Suryaningsih; I Gusti Ayu Rai Widowati; Ni Made Maharianingsih (Journal of Health Community Service, 2025)
Self-medication with antibiotics elevates the threat of resistance, which increases morbidity and mortality. Antibiotic resistance (AMR) in humans must be avoided and reduced. The objective of this community service was to educate housewives about the crucial role of restricting self-medication with antibiotics in the fight against AMR. On March 14, 2023, the Department of Pharmacy at Bali International University executed this community service. The health education intervention was carried out in Banjar Pinda, Gianyar Regency. At least 79 housewives were attending. The event went well, and participants interacted with the presenters enthusiastically. It is implied that community service in Banjar Pinda-Gianyar imparts knowledge about health and the importance of AMR awareness. This program should be expanded to involve other community groups such as craftsmen, the elderly, and young people.